2005
DOI: 10.1038/nsmb911
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of archaeal toxin-antitoxin RelE–RelB complex with implications for toxin activity and antitoxin effects

Abstract: The Escherichia coli chromosome encodes toxin-antitoxin pairs. The toxin RelE cleaves mRNA positioned at the A-site in ribosomes, whereas the antitoxin RelB relieves the effect of RelE. The hyperthermophilic archaeon Pyrococcus horikoshii OT3 has the archaeal homologs aRelE and aRelB. Here we report the crystal structure of aRelE in complex with aRelB determined at a resolution of 2.3 A. aRelE folds into an alpha/beta structure, whereas aRelB lacks a distinct hydrophobic core and extensively wraps around the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
205
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(219 citation statements)
references
References 39 publications
11
205
2
1
Order By: Relevance
“…On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51). Therefore, the common genetic organization, transcriptional regulation, and cellular targets (i.e., translation) of type II TA loci suggest that these gene families emerged by convergent evolution.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51). Therefore, the common genetic organization, transcriptional regulation, and cellular targets (i.e., translation) of type II TA loci suggest that these gene families emerged by convergent evolution.…”
Section: Discussionmentioning
confidence: 84%
“…In E. coli, relBE appears to be part of a complex bacterial response to nutrient starvation (60). Importantly, a crystal structure of the RelBE protein-protein complex was recently solved (61).…”
Section: Discussionmentioning
confidence: 99%
“…Then we subjected the ribosome profile fractions to Western blotting analysis using antibodies to His-tag, because aRelE was prepared with His-tag at its C-terminus, as described previously. 15) The results indicated that aRelE bound the 70S ribosome only in the presence of the mRNAs (Fig. 3A, c-f), though no aRelE was detected in the 70S ribosome fractions in the absence of mRNA (Fig.…”
mentioning
confidence: 83%
“…15) A mutation of Arg85 in aRelE significantly reduced protein synthesis inhibitory activity. 15) In this study, to examine the involvement of Arg85 in inhibitory activity in more detail, Arg85 was replaced by Glu, Trp, His, and Lys, and the resulting mutants were prepared in the same manner as the wild-type and were characterized with respect to inhibitory activity using the E. coli T7 S30 Extract System, as described previously. 15) Figure 2 shows the inhibitory profiles of the mutants.…”
mentioning
confidence: 98%
See 1 more Smart Citation